Learner Needs Analysis for T&I Program Reform - Jeong, Cheol-Ja (Meta, 2005)
AbstractThis paper attempts to reflect learners’ perspectives of the program in a program reform through learner needs analysis that is often neglected in the practice of program renewal. It uses a questionnaire survey conducted with both current and past students of the program to investigate the learners’ target markets and areas of work, checking if the current content of teaching can prepare the learners for such target situations. It also looks into the results of the needs analysis for any discrepancy between the needs ‘perceived by the teachers’ and the ones ‘felt by the learners’. Based on the results of such analysis, a program renewal is proposed to better coordinate the interests and views of the parties involved in the teaching and learning.